2012
DOI: 10.1107/s1744309112042650
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of domains involved in self-assembly of the S-layer protein SbsC

Abstract: The Gram-positive bacterium Geobacillus stearothermophilus ATCC 12980 is completely covered with a two-dimensional crystalline monolayer composed of the S-layer protein SbsC. In order to complete the structure of the full-length protein, additional soluble constructs containing the crucial domains for selfassembly have been successfully cloned, expressed and purified. Crystals obtained from three different recombinant constructs yielded diffraction to 3.4, 2.8 and 1.5 Å resolution. Native data have been collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Although enormous efforts were made to elucidate the atomic structure of S-layer proteins by X-ray crystallography, it turned out that originally only truncated forms were accessible, as only these formed three-dimensional crystals [72][73][74]. The first full-length structure of an S-layer protein, namely the S-layer protein SbsB of Geobacillus stearothermophilus PV72/p2 [21], was obtained in 2012 by making use of the nanobody-aided crystallization approach [47].…”
Section: 11 X For Peer Review 8 Of 18mentioning
confidence: 99%
“…Although enormous efforts were made to elucidate the atomic structure of S-layer proteins by X-ray crystallography, it turned out that originally only truncated forms were accessible, as only these formed three-dimensional crystals [72][73][74]. The first full-length structure of an S-layer protein, namely the S-layer protein SbsB of Geobacillus stearothermophilus PV72/p2 [21], was obtained in 2012 by making use of the nanobody-aided crystallization approach [47].…”
Section: 11 X For Peer Review 8 Of 18mentioning
confidence: 99%
“…6 However, the details of the interactions between liposomes and Slp remain unclear. In recent years, a series of electron microscopy technologies, such as the thinsectioned, freeze-dried, and freeze-etched methods, 30,[71][72][73][74][75][76][77][78] have been adopted to elucidate the location and ultrastructure of Slp lattices. In addition, information on lattice constants, such as average size, was provided by atomic force microscopy 31,[79][80][81][82][83] and small-angle X-ray scattering.…”
Section: Interactions Between Slp and Liposomesmentioning
confidence: 99%
“…89 Native and heavy-atom derivative data confirmed the results of the secondary-structure prediction, which indicated that the N-terminal region comprising the first 257 amino acids is mainly organized as α-helices, whereas the middle and C-terminal parts of SbsC consist of loops and β-sheets. 90,91 The crystal-structure model of truncated rSbsC revealed a novel fold, consisting of six separate domains, which are connected by short flexible linkers. Instead of a dissection approach, Baranova et al used a nanobody-aided crystallization system and provided the first 3-D crystal structure of the nontruncated S-layer protein SbsB from Lysinibacillus sphaericus (formerly Bacillus sphaericus ) CCM 2177 with a resolution of 2.4Å.…”
Section: Introductionmentioning
confidence: 99%